Clinical efficacy of perampanel for partial-onset and primary generalized tonic-clonic seizures - Besag F; Patsalos P (Neuropsychiatric Disease and Treatment)
Frank MC Besag,1–3 Philip N Patsalos4,51East London Foundation NHS Trust, 2Institute of Psychiatry, Psychology and Neuroscience, 3UCL School of Pharmacy, 4Department of Clinical and Experimental Epilepsy, UCL Institute of Neurology, NIHR University College London Hospitals Biomedical Research Centre, London, 5Epilepsy Society, Chalfont Centre for Epilepsy, Chalfont St Peter, UKBackground and purpose: Perampanel, a selective noncompetitive antagonist at the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor, is highly effective in a wide range of experimental models. Although initially licensed as adjunctive therapy for partial seizures with or without secondary generalization in patients aged 12 years or older, the US Food and Drug Administration has recently approved its use in the treatment of primary generalized tonic–clonic seizures (PGTCS). This paper reviews the pharmacokinetics, efficacy, and tolerability of perampanel as an antiepileptic drug.Results: After oral ingestion, perampanel is rapidly absorbed (Tmax, 0.5–2.5 hours), has a bioavailability of ~100%, and is highly protein bound (~95%) in plasma. It undergoes extensive (>90%) hepatic metabolism, primarily via cytochrome P450 3A4 (CYP3A4), with a half-life of 48 hours. Carbamazepine and other antiepileptic drugs can enhance its metabolism via induction of CYP3A4. Efficacy of perampanel in focal seizures has been extensively evaluated in Phase II and randomized, placebo-controlled Phase III trials. The efficacy in PGTCS has been reported in one class I study. In the treatment of focal seizures, perampanel showed significant dose-dependent median seizure reductions: 4 mg/d, 23%; 8 mg/d, 26%–31%; 12 mg/d, 18%–35%; and placebo, 10%–21%. The 50% responder rates were 15%–26%, 29%, 33%–38%, and 34%–36% for placebo, 4 mg/d, 8 mg/d, and 12 mg/d perampanel, respectively. Freedom from seizures was recorded in 0%–1.7% of the placebo group, 1.9% of the 2 mg group, 2.6%–4.4% of the 8 mg group, and 2.6%–6.5% of the 12 mg group. For PGTCS, the median seizure reduction was 76.5% for perampanel and 38.4% for placebo. The 50% responder rate was 64.2% for perampanel and 39.5% for placebo. Seizure freedom during maintenance phase was 30.9% for perampanel and 12.3% for placebo. Adverse effects included dose-dependent increases in the frequency of dizziness, somnolence, fatigue, irritability, falls, and probably nausea.Conclusion: Perampanel is effective in treating both partial-onset seizures and PGTCS.Keywords: perampanel, new antiepileptic drug, epilepsy, primary generalized seizures, pharmacokinetics